Development and Implementation of Hospital Formulary - CW, Shashikala; MS, Ganachari; T, Praveen (Indian Journal of Pharmacy Practice)
Medicine plays a crucial role in the prevention and treatment of diseases. World Health Organization (WHO) model formulary defines a formulary is a manual containing clinically oriented summaries of pharmacological information about selected drugs. Hospital formularies originally started life in hospitals as a collection of commonly prescribed pharmaceutical preparations, produced mainly for reference purposes. As time went on, the hospital formulary was adapted to incorporate the detailed information on the increasing number and diversity of medicines. Till now in India only few hospitals viz. Kasturba Medical College Hospital, Manipal, Karnataka and Christian Medical College Hospital, Vellore, Tamilnadu had developed and implemented formularies which had been effectively utilized in these hospitals. Hence, developed formulary will be useful for reducing the brands available in the hospital which helps in rational drug use. The formulary aims to provide physicians, pharmacists and other healthcare professionals working under hospital to update information about the use of medicines and hence the central goals of the formulary are to help prescribers in the appropriate choice of treatment and to make prescribers follow uniform choice of treatment. The implementation of the formulary will have significant impact on health care professionals' clinical practice to upgrade indirectly the quality of life in the patients, by promoting rational use of prescriptions and proper utilization of drugs. It provides impartial drug information to counteract biased promotional activities. It can be used as a tool to rationalize the range of medicines.
Keywords: Hospital Formulary; Rational Drug Use; Prescription